2010
DOI: 10.1177/183693911003500307
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Implementation: Decisions of Early Childhood Teachers

Abstract: ThE EnGAGEMEnT oF EArly ChIlDhooD teachers with curriculum initiatives reflects the decisions and factors surrounding an educator's relationship with a single curriculum initiative or across multiple curriculum initiatives. Factors such as the available form of professional development and workload intensity may influence decisions teachers make. This paper presents the results of an investigation of the decisions early childhood teachers made about their engagement with state government curriculum initiatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…The director was seen as the principal designer of the work environment, making decisions about organisational structures and therefore creating conditions conducive to PL. The director's ability to support collaborative professional dialogue was a critical component of PD&L, revealing the specialist nature of the director's leadership role and the importance of pedagogical knowledge (Fasoli et al 2007), fundamental in guiding educators in practitioner research linked to everyday practice (Fleet et al 2009, Burgess et al 2010. Findings from this study revealed the complexity of the director's PL support role and the subtleties required in leading professional dialogue and inquiry, knowing when to make decisions about how, when and where to intervene to guide staff learning or to step back to allow exploration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The director was seen as the principal designer of the work environment, making decisions about organisational structures and therefore creating conditions conducive to PL. The director's ability to support collaborative professional dialogue was a critical component of PD&L, revealing the specialist nature of the director's leadership role and the importance of pedagogical knowledge (Fasoli et al 2007), fundamental in guiding educators in practitioner research linked to everyday practice (Fleet et al 2009, Burgess et al 2010. Findings from this study revealed the complexity of the director's PL support role and the subtleties required in leading professional dialogue and inquiry, knowing when to make decisions about how, when and where to intervene to guide staff learning or to step back to allow exploration.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, transmissive modes of PD may result in superficial adoption of new curriculum with little or no change in existing practices (Burgess et al 2010, Nuttall 2013, such as the use of the language and structure of a new curriculum without adopting new pedagogical practices (Winter 2003) or through interpreting frameworks as prescriptive (Ortlipp et al 2011, Pirard 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a paradigm shift that started already in 1977 from being an education based on a seminar tradition to one based on a scientific ground (Brodin and Renblad 2013). Quality in preschool is, according to many researchers, dependent upon scientifically-based teacher training in combination with practical experiences (e.g., Burgess et al 2010;Wang et al 2008). The Swedish preschool teacher training is a profession in transition as the educators are part of the global society (Sheridan et al 2011).…”
Section: Lifelong Learning Starts In Preschoolmentioning
confidence: 98%
“…The educators' responsibility for pedagogical issues has increased and-based on the Swedish curriculum (Lpfö 98/2010)-the preschool is expected to be more learningoriented and of higher quality. Burgess et al (2010) studied an Australian curriculum initiative and found that selfinitiated learning or external teacher training was not suitable in the preschool context if the educators did not receive systematic and contextual support. Another result was that many educators were not motivated to adopt the design of the curriculum and they showed little interest in or engagement to make changes (ibid.).…”
Section: Lifelong Learning Starts In Preschoolmentioning
confidence: 99%